Containing the risk of catastrophic climate change - Heesterman, Aart Reinier Gustaaf (Clean Technol Environ Policy, 2020)
ABSTRACT: There is a general perception that limiting emissions of carbon dioxide will be sufficient to avoid catastrophic climate change. The reality could well be that the many of the world’s wealthy coastal cities which historically developed as ports will be inundated repeatedly to disappear eventually below the sea, with large swathes of the earth being flooded. Other major conurbations may cease to be liveable without air conditioning, while large numbers of people could well starve as a result of disruption of ecosystems. To the extent that this possibility is recognized, it is nevertheless perceived as a gradual process with the worst results in a distance future with any sea-level rise a gradual process. Limiting emissions is unlikely to be sufficient, because the level of carbon dioxide in the earth’s atmosphere is now much higher than ever before since humans started to exploit fossil fuels. We know this from the study of ancient air bubbles in Antarctic ice cores. There is a lack of balance between the energy transmitted by the incoming sunlight and the earth’s outgoing infrared heat radiation. So far this imbalance is absorbed by the enormous thermal mass of the oceans. As to the speed of sea-level rise, a period of extremely rapid sea-level rise of about 1.4 cm per year has occurred in the prehistoric past and disintegration of ice sheets as is happening currently may well be a plausible explanation of this fact. In fact, it is straightforward to create substantial amounts of negative emissions of carbon dioxide. Nevertheless, making it happen will require an unprecedented degree of global cooperation, a high level of taxation on the extraction of coal and crude oil, and the use of pressurized liquid petrol gas as aviation fuel. GRAPHIC ABSTRACT: [Image: see text]